2013
DOI: 10.1111/lasr.12029
|View full text |Cite
|
Sign up to set email alerts
|

The Privatization of Public Safety in Urban Neighborhoods: Do Business Improvement Districts Reduce Violent Crime Among Adolescents?

Abstract: The business improvement district (BID) is a popular economic development and urban revitalization model in which local property and business owners must pay an assessment tax that funds supplementary services, including private security. BIDs constitute a controversial form of urban revitalization to some because they privatize economic development and public safety efforts in public space. This study examines whether BIDs provide tangible benefits beyond their immediate boundaries to local residents in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…BIDs have been shown to influence their local communities in many ways (Brooks, 2008). Relevant to this study, research suggests creating BIDs is associated with crime reductions in the local area (Brooks, 2008; Cook & MacDonald, 2011; Hoyt, 2004; MacDonald, Stokes, Grunwald, & Bluthenthal, 2013). However, crime and place research has also consistently shown that crime is disproportionately concentrated within select places (e.g., Andresen & Linning, 2012; Andresen & Malleson, 2011; Pierce, Spaar, & Briggs, 1988; Sherman, Gartin, & Buerger, 1989; Weisburd, Groff, & Yang, 2012), particularly if they are places that attract a lot of people (e.g., Bernasco & Block, 2011; Haberman & Ratcliffe, 2015).…”
Section: Introductionmentioning
confidence: 81%
“…BIDs have been shown to influence their local communities in many ways (Brooks, 2008). Relevant to this study, research suggests creating BIDs is associated with crime reductions in the local area (Brooks, 2008; Cook & MacDonald, 2011; Hoyt, 2004; MacDonald, Stokes, Grunwald, & Bluthenthal, 2013). However, crime and place research has also consistently shown that crime is disproportionately concentrated within select places (e.g., Andresen & Linning, 2012; Andresen & Malleson, 2011; Pierce, Spaar, & Briggs, 1988; Sherman, Gartin, & Buerger, 1989; Weisburd, Groff, & Yang, 2012), particularly if they are places that attract a lot of people (e.g., Bernasco & Block, 2011; Haberman & Ratcliffe, 2015).…”
Section: Introductionmentioning
confidence: 81%
“…Research carried out by Caruso and Weber (2006) contrasts other scholars’ conclusions supporting the accountability and innovation that BIDs provide by finding that residents and local government officials have minimal oversight of BIDs, while pointing out that improvement districts are able to use public funds to pursue private agendas. MacDonald et al (2013) also concluded that BIDs have the ability to act without the full consideration of resident interests as a result of being neither wholly private nor public entities. Lewis (2010) observed that BIDs can be successful in promoting urban revitalization, however they concurrently pose concerns that include intensifying socioeconomic and spatial inequalities, weakening municipal government, and restricting democratic accountability.…”
Section: Business Improvement Districts: Boost or Barrier?mentioning
confidence: 99%
“…Discerning to whom BIDs should be accountable will also assist in developing accurate standards for performance measurement. Studies pertaining to BIDs have measured their effect on issues such as crime (Hoyt 2005; Macdonald et al 2013), property values (Ellen et al 2007), and tourism (Ratcliffe and Flanagan 2004), however if scholars, practitioners, and policy makers are unable to reach consensus on who BIDs should be accountable to we will be unable to determine if they are sufficiently and successfully serving those they are designed to benefit. Since BIDs are authorized under state law in the United States, organization structures and legal framework for districts differ in cities dependent on the state in which they are established.…”
Section: Conclusion and Future Implicationsmentioning
confidence: 99%
“…Originating in Toronto, the BIA model has now been widely adopted across Canada and elsewhere in the world (note BIAs are known as Business Improvement Districts (BID) in the UK, the United States, and elsewhere). The BIA model has showed its durability and commitment through systematic increases in their scale, scope, and role; however, the concept has not been devoid of controversy (Hogg et al 2003;Miraftab 2004;Hoyt 2005aHoyt , 2006Baer 2008;Hernandez and Jones 2008;Mor S c€ ol and Zimmermann 2008;Ward 2010;MacDonald and Grunwald 2013). Following widespread adoption across North America, the BIA concept was most recently introduced in Europe as a "milder" public private partnership under the Town Centre Management (TCM) model (Schiller 1994;Whyatt 2004;Cook 2008;Hogg et al 2007;Ysa 2007;Reeve 2008;Bovaird 2010;Hammerschmid and Ysa 2010).…”
Section: Introductionmentioning
confidence: 99%